(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Twitter monitoring enables firms to consider their market, stay on track of what is being said regarding their company and contenders, and uncover emerging market trends. Twego Trending is a platform where data will be viewed and structured by an automated procedure of analyzing and processing tweets data and classifying it into various hash statistics and visualizations. Implementing Twego forecasting analysis on Twitter data using various technologies may help businesses know how consumers talk about their product. Twitter has more than 340 million active users and almost 500 millions tweets are posted every day. This social media platform helps companies to reach a large audience and communicate without intermediaries with consumers. The aim is to build a Search Engine in which , when someone will type in a query , it will return back tweets as well as do data analytics on the results and provide visualizations.